1981
DOI: 10.1126/science.211.4482.540
|View full text |Cite
|
Sign up to set email alerts
|

Organic Farming in the Corn Belt

Abstract: A small minority of farmers in the Midwest produces crops on a commercial scale without using modern fertilizers and pesticides. On the basis of a 5-year study, it appears that these farmers have more in common with the majority of farmers in the region than with certain stereotypes of organic farmers. Their farming practices (other than chemical use), the size and labor requirements of their farms, and the production and profitability they achieve differ from those of conventional farmers by considerably less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
3
5

Year Published

1987
1987
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(103 citation statements)
references
References 11 publications
3
92
3
5
Order By: Relevance
“…Since the biological components of soils respond more rapidly to changing soil conditions than do either physical or chemical properties, they may be regarded as sensitive indicators of soil conditions [16][17][18][19][20]. Studies assessing impacts of organic amendments and cover crops on soil quality in contrasting environments have focused primarily on C-related properties [5,21,22]. This fact is understandable, due to the important role that soil organic matter plays in maintaining soil productivity [5,23]; nonetheless according with recent trends in the analysis of soil quality [24,25], a comprehensive evaluation of multiple functions of soil require the assessment of soil physical, chemical, biochemical, and biological properties and processes.…”
Section: Introductionmentioning
confidence: 99%
“…Since the biological components of soils respond more rapidly to changing soil conditions than do either physical or chemical properties, they may be regarded as sensitive indicators of soil conditions [16][17][18][19][20]. Studies assessing impacts of organic amendments and cover crops on soil quality in contrasting environments have focused primarily on C-related properties [5,21,22]. This fact is understandable, due to the important role that soil organic matter plays in maintaining soil productivity [5,23]; nonetheless according with recent trends in the analysis of soil quality [24,25], a comprehensive evaluation of multiple functions of soil require the assessment of soil physical, chemical, biochemical, and biological properties and processes.…”
Section: Introductionmentioning
confidence: 99%
“…"It is considered that such higher-protein corn is superior feed-stuff." The results for maize, reported by Lockeretz et al (1981) and by Wolfson and Shearer (1981), showed that the crude protein concentration in a conventionally grown crop was significantly higher than that in the organically grown crop. One study has actually shown processed organic products to be less healthy than their conventionally produced equivalents.…”
Section: Organic Food Is More Nutritious?mentioning
confidence: 70%
“…C'est un moment de synthèse où les auteurs se réfèrent aux travaux déjà anciens tels que Printemps silencieux (Carson, 1962), les travaux théo-riques en écologie écosystémique (Odum, 1953) et les travaux fondateurs sur l'analyse des performances de l'AB (Lockeretz et al, 1976 ;Lockeretz et al, 1981). Les années 1980 sont aussi marquées par la citation de travaux d'auteurs de l'agroécologie et de l'agriculture traditionnelle (Gliessman et al, 1981), à l'appui d'une réflexion sur les modalités du développement au Sud (Chambers, 1983).…”
Section: Quelles Convergences Paradigmatiques ?unclassified